2022
DOI: 10.1097/prs.0000000000008712
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Expander-to-Implant Exchange after Irradiation in Immediate Two-Stage Breast Reconstruction

Abstract: Background: Time intervals for expander-to-implant exchange from radiation therapy have been reported to reduce device failure. This study investigated the optimal timing of expander-to-implant exchange after irradiation in terms of short-and long-term outcomes. Methods: This retrospective review enrolled consecutive patients who underwent immediate two-stage breast reconstruction and radiation therapy to tissue expanders from 2010 to 2019. Receiver operating characteristic curves and the Youden index were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, the early exchange group appeared to have a higher rate of infection and the late exchange group had a higher rate of capsular contracture. In 2022, Kim et al [ 38 ] investigated the optimal timing of exchange to reduce the incidence of short‐term (49 days) and long‐term (2 years) complications and found that placing a permanent implant 131 days after radiotherapy reduced the incidence of short‐term complications. At present, the optimal timing of the exchange is still uncertain.…”
Section: Timing Of Pmrt In Patients Undergoing Brmentioning
confidence: 99%
“…However, the early exchange group appeared to have a higher rate of infection and the late exchange group had a higher rate of capsular contracture. In 2022, Kim et al [ 38 ] investigated the optimal timing of exchange to reduce the incidence of short‐term (49 days) and long‐term (2 years) complications and found that placing a permanent implant 131 days after radiotherapy reduced the incidence of short‐term complications. At present, the optimal timing of the exchange is still uncertain.…”
Section: Timing Of Pmrt In Patients Undergoing Brmentioning
confidence: 99%